THE EFFECT OF SPIRITUAL LEADERSHIP ON HAPPINESS AT THE WORKPLACE: AN EXPLORATORY STUDY OF THE OPINIONS OF A SAMPLE OF FACULTY MEMBERS IN FACULTIES OF ADMINISTRATION AND ECONOMIC IN A NUMBER OF UNIVERSITIES IN THE KURDISTAN REGION OF IRAQ - Saleem, Vaheen; Dawoda, Range (Humanities Journal of University of Zakho, 2024)
The research aims to present the concept of Spiritual Leadership, which is one of the contemporary concept in the field of leadership, and its role in Happiness in the workplace as a concept that falls under the positive aspects of the individual to ensure the individual and collective performance of the organization as a whole, the research aims mainly to test the correlation between spiritual leadership and happiness in the workplace among faculty members, as well as to diagnose the impact of the dimensions of spiritual leadership on happiness in the workplace, The descriptive analytical methodology has been adopted to diagnose research variables and test hypotheses in administration and economic colleges of universities in the Kurdistan Region of Iraq, including (17) universities, and the sample consisted of (287) of faculty staff in the surveyed universities, who indicated their opinion regarding their agreement on the questionnaire. The data were analyzed based on a number of statistical tools, including mean, standard deviations, correlation analysis and regression, the research concluded that there is a significant correlation between spiritual leadership and happiness in the workplace and that happiness in the workplace among faculty members is associated with the availability of dimensions of spiritual leadership among administrative leaders in the universities surveyed. the research recommended the need to provide Indicators that express the spiritual aspects of leadership in order to enhance the levels of happiness in the workplace among faculty members, as well as to suggest other variables that can affect the levels of happiness in the workplace within the framework of future studies.